Epidemiologic and clinical characteristics of selected congenital anomalies at the largest Bosnian pediatric surgery tertiary center. Issue 48 (2nd December 2022) - Zvizdic, Zlatan; Becirovic, Naida; Milisic, Emir; Jonuzi, Asmir; Terzic, Sabina; Vranic, Semir
Abstract : Congenital anomalies (CA) are any abnormality present at birth, either structural or functional, that may potentially affect an infant's health, development, and/or survival. There is a paucity of studies on clinical characteristics and outcomes of CA in Bosnia and Herzegovina, mainly due to the lack of a nationwide congenital malformations monitoring system. A 5-year hospital-based study was conducted to determine the prevalence at birth and clinical characteristics of selected major CA in Sarajevo Canton, Bosnia and Herzegovina. Ninety-one CA were observed from 2012 to 2016 (the overall prevalence was 39.6 cases/10, 000 live births). The mean age of neonates at diagnosis was 3 days. The gastrointestinal tract was the most commonly affected system (76.9%), with esophageal atresia (EA) being the most frequent (17.6% of all CA). Major CA were more prevalent among preterm infants than term infants ( P = .001), particularly in males (61.5% vs. 38.5%; P = .028; M:F ratio was 1.59). Multiple CA were seen in 37.4% of neonates. The overall mortality rate of neonates was 11%, and the median length of hospital stay was 19.8 days. Our study revealed the distribution and clinical patterns of common major CA in the largest tertiary care facility in Bosnia and Herzegovina. It also confirmed a relatively high mortality rate, which requires further efforts to improve the quality of neonatal care in the country.